THE OUTBURST OF MODERN MARKET DEVELOPMENT (HYPERMART, MALL AND THE KINDS) - Murni Ediati (TEKNIK, 2009)
Urban areas in Indonesia have tended to grow with little control or order in recent years, and this problemincludes the problem of modern markets. The emergence of modern market centers in Indonesia has given anew color to commerce activities. Opinions pro and contra have appeared about the emergence of thesecommercial centers. There are the various interests and needs of the actors such as investors, society, andgovernment in the emergence of malls, plazas, hypermarts, and groceries. The interests focus on the need toimprove tax revenue, regional compensation, inclusion of employees, improvement of trade, and the fulfillmentof people living standbards. Recently, the fast-growing modern markets have caused many controversies.However, government policies and decisions still support the emergence of such modern trade centers. Thesemodern markets compete with traditional markets. Although the traditional markets have their own marketsegments, modern markets should not allowed to wipe out them out. Based on these reasons, therefore, thegovernment should make strict, fair, and neutral regional policies (regional regulation) such as zoning rule andurban planning concepts for upcoming 50 years. Moreover, the government should improve the role oforganizers and urban planners as the managers, and enrich the market with pluralistic and comprehensiveconcepts sustainable development and social participation, something which is often neglected in urbanplanning.